Subinhibitory Concentrations of Clinically-Relevant Antimicrobials Affect Resistance-Nodulation-Division Family Promoter Activity in Acinetobacter baumannii - Prieto Martin Gil, Sonia; Tajuelo, Ana; López-Siles, Mireia; McConnell, Michael J. (Frontiers in Microbiology, 2021)
Efflux pumps contribute to multidrug resistance in Acinetobacter baumannii due to their ability to expel a wide variety of structurally unrelated compounds. This study aimed to characterize the effect of subinhibitory concentrations of clinically-relevant antibiotics and disinfectants on the promoter activity of members of the Resistance-Nodulation-Division (RND) family in A. baumannii. The promoter regions from three RND efflux pumps (AdeABC, AdeFGH and AdeIJK) and the AdeRS regulatory system from three different A. baumannii strains (ATCC 17961, ATCC 17978 and ATCC 19606) were cloned into a luciferase reporter system (pLPV1Z). Promoter activity was quantitatively assessed in both exponential and stationary phase cultures after exposure to subinhibitory concentrations of four antibiotics from different classes (rifampicin, meropenem, tigecycline and colistin) and two disinfectants (ethanol and chlorhexidine). Subinhibitory concentrations of the compounds tested had variable effects on promoter activity that were highly dependent on the A. baumannii strain, the compound tested and the growth phase. Fold changes in AdeABC promoter activity ranged from 1.97 to 113.7, in AdeFGH from -5.6 to 1.13, in AdeIJK from -2.5 to 2, and in AdeRS from -36.2 to -1.32. Taken together, these results indicate that subinhibitory concentrations of clinically-relevant antibiotics and disinfectants affect the promoter activity of RND family members in A. baumannii in a strain and growth phase dependent manner. These results may have important implications for the treatment of infections caused by A. baumannii.